A Telemedicine Approach to Increase Treatment of Alcohol Use Disorder in Primary Care: A Pilot Feasibility Study. Issue 1 (January 2021) - Leibowitz, Amy; Satre, Derek D.; Lu, Wendy; Weisner, Constance; Corriveau, Caroline; Gizzi, Elio; Sterling, Stacy
Abstract : Background and Aims: Unhealthy drinking is a leading threat to health, yet few people with alcohol use disorder (AUD) receive treatment. This pilot tested the feasibility of addiction medicine video consultations in primary care for improving AUD medication adoption and specialty treatment initiation. Methods: Primary care providers (PCPs) received training and access to on-call addiction medicine consultations. Feasibility measures were training attendance, intention to use the service and/or AUD pharmacotherapy, and user feedback. Secondary outcomes were utilization, prescription and treatment initiation rates, and case reports. χ 2 tests were used to compare prescription and treatment initiation rates for consult recipients and non-recipients. Results: Ninety-one PCPs (71.1%) attended a training, and 60 (65.9%) provided feedback. Of those, 37 (64.9%) mentioned pharmacotherapy and 41 (71.9%) intended to use the video consult service. Of 27 users, 19 provided feedback; 12 (63.1%) rated its value at 8 or above, on a scale of 1 to 10 (average 6.9). The most useful aspect was immediacy, and users wanted an easier workflow and increased consultant availability. Of 32 patients who received a consult, 11 (34.4%) were prescribed naltrexone, versus 43 (6.4%) of non-recipients ( P  < 0.0001); 11 (34.4%) initiated specialty treatment, versus 105 (19.7%) of non-recipients ( P  < 0.05). Conclusions: PCP training attendance and feedback suggest that an addiction telemedicine consult service would be valuable to PCPs and might increase AUD medication uptake and specialty addiction treatment initiation. However, future research should include significant modifications to the piloted telemedicine model: robust staffing and simpler, more flexible methods for PCPs to obtain consults.